Behavior of Political Elite Taxpayers and Political Connections to Tax Obligations during the COVID-9 Pandemic - Megawanti Megawanti; Alimuddin; Nirwana (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This research focuses on the behavior of political elite taxpayers and their political connections during the COVID-19 pandemic. The research object is the political elite, entrepreneurs, and entrepreneurs who have connections with the political elite in Balikpapan. Using Husserl's transdental phenomenological study to gain an in-depth understanding of the behavior and meaning of tax with tax subjects using the terms